Identification of hidden health utilization services and costs in adults awaiting tertiary care following mild traumatic brain injury in Toronto, Ontario, Canada - Cindy Hunt; Katrina Zanetti; Brian Kirkham; Alicja Michalak; Cheryl Masanic; Chantal Vaidyanath; Shree Bhalerao; Michael D Cusimano; Andrew Baker; Donna Ouchterlony (Concussion)
Aim: The cognitive, emotional, behavioral and physical impairments experienced by adults after mild traumatic brain injury (mTBI) can produce substantial disability, with 15–20% requiring referral to tertiary care (TC) for persistent symptoms. Methods: A convenience sample of 201 adult patients referred to TC as a result of mTBI was studied. Self-reported data were collected at first TC visit, on average 10 months postinjury. Patients reported the type and intensity of healthcare provider visit(s) undertaken while awaiting TC. Results: On average males reported 37 and females 30 healthcare provider visits, resulting in over $500,000 Canadian dollars spent on potentially excess mTBI care over 1 year. Discussion: Based on conservative estimate of 15% of mTBI patients receiving TC, this finding identifies a possible excess in care of $110 million for Ontario. Accurate diagnosis of mTBI and early coordination of follow-up care for those needing TC could increase cost–effectiveness.